Salt‐induced aggregation of a monoclonal human immunoglobulin G1. Issue 2 (12th November 2012) - Rubin, Jonathan; Linden, Lars; Coco, Wayne M.; Bommarius, Andreas S.; Behrens, Sven H.
Abstract Physical stability is critical for any therapeutic protein's efficacy and economic viability. No reliable theory exists to predict stability de novo, and modeling aggregation is challenging as this phenomenon can involve orientation effects, unfolding, and the rearrangement of noncovalent bonds inter‐ and intramolecularly in a complex sequence of poorly understood events. Despite this complexity, the simple observation of protein concentration‐dependent diffusivity in stable, low ionic‐strength solutions can provide valuable information about a protein's propensity to aggregate at higher salt concentrations and over longer times. We recently verified this notion using two model proteins, and others have shown that this strategy may be applicable to antibodies as well. Here, we expand our previous study to a monoclonal human immunoglobulin G1 antibody and discuss both merits and limitations of stability assessments based on the diffusional virial coefficient kD. We find this parameter to be a good predictor of relative protein stability in solutions of different chaotropic salts, and a telling heuristic for the effect of kosmotropes. Both temperature and glycosylation are seen to have a strong influence on kD, and we examine how these factors affect stability assessments. Protein unfolding is monitored with a fluorescence assay to assist in interpreting the observed aggregation rates. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:377–386, 2013